Students Written Production Error Analysis in the EFL Classroom Teaching: A Study of Adult English Learners Errors - Sihombing, Ranauli; Nissa, Astri Khoirun; Estrelita, Amelia (LLT Journal: A Journal on Language and Language Teaching, 2015)
Errors analysis has become one of the most interesting issues in the study of Second Language Acquisition. It can not be denied that some teachers do not know a lot about error analysis and related theories of how L1, L2 or foreign language acquired. In addition, the students often feel upset since they find a gap between themselves and the teachers for the errors the students make and the teachers understanding about the error correction. The present research aims to investigate what errors adult English learners make in written production of English. The significances of the study is to know what errors students make in writing that the teachers can find solution to the errors the students make for a better English language teaching and learning especially in teaching English for adults. The study employed qualitative method. The research was undertaken at an airline education center in Bandung. The result showed that syntax errors are more frequently found than morphology errors, especially in terms of verb phrase errors. It is recommended that it is important for teacher to know the theory of second language acquisition in order to know how the students learn and produce theirlanguage. In addition, it will be advantages for teachers if they know what errors students frequently make in their learning, so that the teachers can give solution to the students for a better English language learning achievement.